Gender wage discrimination in the Turkish labor market - Cudeville, Elisabeth; Gurbuzer, Leman Yonca (Paris, 2007)
"While the topic of gender equality turns out to be an important element in the preparation of Turkey to join the European Union, very little empirical research on this issue has been done using Turkish data. This paper aims to contribute toward filling this gap. We propose an estimate of the wage discrimination in Turkey relying on different decompositions of the gender waga differential. The data set used is the 2003 Turkish Household Budget Survey. In Turkey, the observed average gender wage gap is about 25,2 % in favor of men for the salaried population and around 60 % of it may be attributed to discrimination. In terms of gender wage discrimination, with an observed wage gap close to those observed in France and Italy, and a discrimination component close to the ones obtained in Spain and Greece with comparable methods, Turkey happens to do not so bad. But, in the Turkish case, wage discrimination appears to be a bad indicator of gender inequalities in the labor market, as exclusion and segregation of women are the main concerns."